2010
DOI: 10.1007/s10875-010-9448-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Functions of Peripheral Blood Monocyte Subpopulations in Aged Humans

Abstract: Aging is associated with increased susceptibility to microbial infections, and monocytes play an important role in microbial defense. In this study, we have identified and compared four subpopulations of monocytes (CD14++(high)CD16−, CD14+(low)CD16−, CD14++(high)CD16+, and CD14+(low)CD16+) in the peripheral blood of young and aged subjects with regard to their numbers, cytokine production, TLR expression, and phosphorylation of ERK1/2 in response to pam3Cys a TLR-1/2 ligand. Proportions and numbers of CD14++(h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
137
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(158 citation statements)
references
References 29 publications
14
137
2
5
Order By: Relevance
“…29,[53][54][55][56] This "activated pattern" is confirmed by the expansion of CD11b expression and by the reduction of CD38, CD62L, and CD115 expression. Plasma levels of soluble CD163 (sCD163) and CXCL10, markers of innate immune activation, increase with age.…”
Section: B-cells Responsementioning
confidence: 80%
“…29,[53][54][55][56] This "activated pattern" is confirmed by the expansion of CD11b expression and by the reduction of CD38, CD62L, and CD115 expression. Plasma levels of soluble CD163 (sCD163) and CXCL10, markers of innate immune activation, increase with age.…”
Section: B-cells Responsementioning
confidence: 80%
“…In fact, early studies reported increased, unchanged, and decreased LPS-induced cytokine secretion [69]. However, more recently, an age-related reduction in IL-6 production by monocytes in response to TLR1/2 ligand has been demonstrated [76]. In addition, van Duin et al also reported reduced TLR1/2-induced TNF-α and IL-6 production by monocytes from older individuals using fl ow cytometry [77].…”
Section: Tlr Activationmentioning
confidence: 99%
“…71 Despite relatively few changes in the absolute numbers of monocytes, the distribution of the different subsets is changed, characterized by a marked reduction in classical monocytes and an increased frequency of intermediate and non-classical monocytes in older or HIV infected patients. [72][73][74] These CD16 C monocytes are increased during the infection and are correlated with viremia, T cell activation, and with plasma levels of IL-6. They are expanded in patients who do not take therapy or discontinue treatment.…”
Section: Over-representation Of Cd16mentioning
confidence: 99%